Administration of Testate Estates: A Malaysian Identity - Halim, Akmal Hidayah (2012)
When a person dies and leaves behind a will, he is said to have died testate. In Malaysia, regardless of the estate value, the High Court has the jurisdiction to deal with a testate estate by virtue of section 24(f) of the Courts of Judicature Act 1964 (Act 91). The jurisdiction of the High Court relating to the grant of probate and letters of administration to the executor and administrator respectively is exclusive in any case where the deceased has left a valid will or other testamentary disposition. Nevertheless, as for the estate of a Muslim who dies testate, the nature of the will needs to be ascertained. This is due to the reason that the application for the administration of the estate will have to be made at the High Court only in cases where the will contains the appointment of an executor that necessitates the application for probate. If there is no such provision and the will only contains the disposition of the deceased’s property, the jurisdiction to deal with the validity of such will lies with the Syariah Court. In this respect, it is said that the jurisdiction of the High Court to deal with the testate estates of Muslims is not exclusive. Hence, this paper seeks to analyze the relevant law in the administration of testate estates of both Muslims and non-Muslims in Malaysia. An analysis will also be made to the jurisdiction of the Civil High Court in procedural matters and the jurisdiction of the Syariah Court in substantive matters relating to the Muslims’ wills in Malaysia.